42 Social and economic impact of cervical cancer in brazil: analysis of EVA/EVITA cohort study (LACOG 0215). (18th September 2019) - Nogueira-Rodrigues, A; Melo, A; Calabrich, A; Cronenberger, E; Torres, K; Damian, F; Cossetti, R; Azevedo, C; Fonseca, A; Yeni, N; Nunes, J; Lopes, A; et al.
Abstract : Objectives: Compare marital status, household income and labor activity at diagnosis and at 1-year follow-up among cervical cancer (CC) patients in Brazil. Methods: LACOG 0215 EVITA is a prospective observational study, within 16 Brazilian sites, including 18 years-old, newly diagnosed, stage I to IV invasive CC patients. We present data collected at baseline and at 1-year follow-up regarding demography, histology, stage, marital status, household income and labor activity. Variables were compared using Chi-square test. Results: 593 patients were included in this analysis. 75 (12.6%) were diagnosed in stage I, 452 (76.2%) II-III and 66 (11.2%) IV. Mean age at diagnosis was 57.0, 56.4 and 50.5 years respectively. Squamous cell carcinoma was the most frequent histology. 34.2% of stage I, 30.6% of stage II-III and 24.6% of stage IV patients had 9 or more years of education. About 95% patients had a previous pregnancy history. At 1-year follow-up there was a decrease in the proportion of married patients in stage II-III patients only (53.3% to 47.5%; p-value <0.001). There was a reduction in the proportion of women engaged in labor activity in stage II-III (34.1% to 16.1%; p-value, <0.001) but not in stage I and IV. No difference was found in household income 1 year after diagnosis. Conclusions: CC may impact patients personal and work life long after diagnosis, even in those diagnosed with curable disease. In this cohort, stage II-III CC face more risk of divorce and job losses. Social support following diagnosis and treatment is essential for CC patients.